Estudio crítico sobre el abandono de los templos decretados patrimonio en el norte del departamento del Huila (2022)
When looking for information about the temples, it is evident that there are few documents organized, protected or preserved by both municipal and departmental religious organizations, there are data, but no real evidence of the beginning of the construction, or of the problems, that each temple has suffered, the diagnosis refers, at a general level, to the analysis that is carried out to determine any situation, for this particular case, almost all the information in this analysis was from facts collected in various areas other than the places where they were intended to be found , that is to say that there is not much information on the temples or parishes, so to diagnose the parameters that affect the problem of conservation of the current infrastructure of the temples of Aipe, Neiva and Villavieja, we worked in the municipalities essentially with the population that day by day inhabits the place, it is evident that the passage of time and the inclemency of the climate are the entities, that constructions are more affected, but man also deteriorates heritage, they do not take care of it, because society gives different uses to spaces and constructions, many are responsible for the deterioration and neglect of temples, the religious community, the state, the inhabitants of each municipality, can be insured; that carelessness is participatory, that is, it is the product of everyone.